New European bee species of the tribe Osmiini (Hymenoptera: Apoidea: Megachilidae) - Müller, Andreas (Zootaxa, 2012)
Bees of the tribe Osmiini (Megachilidae) are represented by about 230 described species in Europe. In this publication, 15 newEuropean osmiine bee species are described and diagnosed: Hoplitis (Alcidamea) occidentalis spec. nov., Hoplitis (Anthocopa)peniculifera spec. nov., Hoplitis (Hoplitis) hilbera spec. nov., Hoplitis (Hoplitis) lithodorae spec. nov. and Hoplitis manuelaespec. nov. from Spain; Chelostoma (Chelostoma) siciliae spec. nov. from Sicily; Chelostoma (Foveosmia) incognitum spec.nov., Chelostoma (Foveosmia) longifacies spec. nov., Chelostoma (Gyrodromella) aegaeicum spec. nov., Hoplitis (Annosmia)monticola spec. nov., Hoplitis (Anthocopa) nicolaei spec. nov., Hoplitis (Anthocopa) serainae spec. nov. and Protosmia (Nano-smia) montana spec. nov. from Greece; Chelostoma (Chelostoma) comosum spec. nov. from Cyprus; and Hoplitis (Anthocopa) caucasicola spec. nov. from the Caucasus.